Complications of pregnancy and labour in women with Klippel–Trénaunay syndrome: a nationwide cross‐sectional study. (5th June 2017) - Horbach, SE; Lokhorst, MM; Oduber, CE; Middeldorp, S; van der Post, JA; van der Horst, CM
Abstract : Objective: To evaluate complications of pregnancy, including thromboembolism, in women with extensive vascular malformations associated with Klippel–Trénaunay syndrome (KTS). Design: Nationwide cross‐sectional study. Setting: Two tertiary expert centres and the Dutch Klippel–Trénaunay patient organisation. Sample: Adult women with KTS. Methods: Patients with KTS were invited to participate in a comprehensive online survey about their obstetric history. Reference data on pregnancy outcomes and complications of non‐diseased women were collected from population‐based cohorts from the literature. Main outcome measures: Prevalence of complications, specifically venous thromboembolism and postpartum haemorrhage. Results: Sixty women completed the survey. Seventeen patients did not conceive, of whom three refrained from pregnancy because of KTS. A total of 97 pregnancies and 86 deliveries were reported in 43 patients. KTS‐related symptoms were aggravated during pregnancy in 43% of patients. Deep vein thrombosis was present in 5.8% and pulmonary embolism was present in 2.3% of pregnancies, which was extremely high compared with the reference population ( P < 0.0001), with a relative risk of 108.9 (95% confidence interval, 95% CI 46.48–255.03) and 106.2 (95% CI 26.97–418.10), respectively. Severe postpartum haemorrhage (PPH) occurred in 11% of KTS pregnancies, compared with 5.8% of pregnancies in the reference population (relative risk, RR 1.81, 95% CI 0.97–3.37, P = 0.06). Conclusions: Our data suggest that women with KTS have a significant risk of venous thromboembolic events, severe postpartum haemorrhage, and aggravation of KTS symptoms during pregnancy, and in early postpartum period. Obstetricians should counsel patients about these risks in the preconception phase. Antithrombotic prophylaxis should be considered in the obstetric management of patients with KTS. Tweetable abstract: High risk of complications during pregnancy and labour in women with Klippel–Trénaunay syndrome. Tweetable abstract: High risk of complications during pregnancy and labour in women with Klippel–Trénaunay syndrome.